2020
DOI: 10.1177/1535370220931038
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of exogenous hydrogen sulfide on diaphragm muscle fibrosis in streptozotocin-induced diabetic rats

Abstract: Diabetes mellitus has been shown to impair respiratory function. The diaphragm is an important skeletal muscle involved in respiration. Hydrogen sulfide (H2S) is one of the three endogenous gas messengers in mammals, which exhibits anti-fibrotic activity in some types of diabetes-related complications. However, whether and how H2S exerts its anti-fibrotic activity on the diabetic diaphragmatic muscle remains unclear. In this study, we explored the anti-fibrotic activity of exogenous H2S on the diaphragm using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“… 22 Further, CysSSH is a nucleophile that can protect against oxidative stress in cells. 10 , 23 It is possible that exogenous H 2 S donors supplemented the endogenous H 2 S synthesis in diaphragm fibers during prolonged MV 24 , 25 ; this is a testable hypothesis worthy of future study. Clearly, future studies should investigate the specific role that CysSSH and other sulfur species play in protecting against VIDD.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Further, CysSSH is a nucleophile that can protect against oxidative stress in cells. 10 , 23 It is possible that exogenous H 2 S donors supplemented the endogenous H 2 S synthesis in diaphragm fibers during prolonged MV 24 , 25 ; this is a testable hypothesis worthy of future study. Clearly, future studies should investigate the specific role that CysSSH and other sulfur species play in protecting against VIDD.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is related to the failure of multiple organs and can lead to respiratory dysfunction by reducing the endurance of respiratory muscles and lung capacity. The diaphragm is an important skeletal muscle in the mammalian breathing process [ 137 ]. Excessive inflammation of diabetes often leads to collagen deposition and muscle fibrosis.…”
Section: Protective Effects Of Gasotransmitters In Fibrotic Diseasesmentioning
confidence: 99%
“…Excessive inflammation of diabetes often leads to collagen deposition and muscle fibrosis. However, one recent study demonstrated that administration of NaHS could ameliorate hyperglycemia-induced diaphragm muscle fibrosis and improved the diaphragmatic biomechanical properties in diabetes mellitus, which might be associated with the alleviation of collagen deposition through the suppression of NLRP3 inflammasome-mediated inflammatory reaction [ 137 ]. This report confirmed that the therapeutic strategies aimed at inhibiting NLRP3 inflammasome-mediated fibrosis by utilizing exogenous H 2 S might serve as efficient targeted therapy in diabetes mellitus.…”
Section: Protective Effects Of Gasotransmitters In Fibrotic Diseasesmentioning
confidence: 99%
“…43 H 2 S protects diaphragm muscle fibrosis and strengthens diaphragmatic biomechanical properties in streptozotocin-induced diabetic rats. 44 H 2 S also alleviates the injury of skeletal muscle in ischemia-reperfusion rats, improves muscle functions in high-fat-diet-fed mice, and increases muscle mass in db/db diabetic mice. 20,43,45,46 We and others recently discovered that H 2 S suppresses angiotensin II or hyperhomocysteinemia-induced skeletal muscle atrophy in mice via mitigation of endoplasmic reticulum stress and Golgi's stress response.…”
Section: Introductionmentioning
confidence: 95%
“…H 2 S induces the S ‐sulfhydration of Kv7 channel proteins and contributes to skeletal muscle hypercontractility in human malignant hyperthermia syndrome 43 . H 2 S protects diaphragm muscle fibrosis and strengthens diaphragmatic biomechanical properties in streptozotocin‐induced diabetic rats 44 . H 2 S also alleviates the injury of skeletal muscle in ischemia‐reperfusion rats, improves muscle functions in high‐fat‐diet‐fed mice, and increases muscle mass in db/db diabetic mice 20,43,45,46 .…”
Section: Introductionmentioning
confidence: 99%